Long time release of water soluble drug from hydrophilic nanofibrous material. Issue 36 (7th May 2019) - Pan, Nan; Qin, Juanrong; Fan, Yuwei; Li, Zeke; Song, Botao
ABSTRACT: In this study, mesoporous silica nanoparticles (MSNs) were embedded into the hydrophilic poly(vinyl alcohol) (PVA) nanofibrous mats to achieve sustained release of water soluble drug from hydrophilic nanofibrous mats. MSNs were successfully prepared based on a sol–gel method. Water soluble drug naproxen sodium was then loaded into the mesopores of the MSNs, and different amounts of the drug‐loaded MSNs were further incorporated into the fibers by the electrospinning process. Morphology of the nanofibrous mats was investigated, and it was found that all the fibers exhibited fibrous structure. Interestingly, lots of protrusions could be observed from the scanning electron microscopy images with high magnification, and numbers of the protrusions increased with the increasing of loading ratios of the MSNs from 5 to 15%. In addition, the wetting behaviors of the nanofibrous mats were also measured, and the water contact angles of all the mats were measured to be 0°. Finally, the drug release results indicated that all the PVA/MSNs composite nanofibrous mats showed an obviously prolonged drug release. The optimal loading ratio of the MSNs in the nanofibers was 10% due to the slowest drug release rate. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47922. Abstract :